2016
DOI: 10.18632/oncotarget.13086
|View full text |Cite
|
Sign up to set email alerts
|

ERN1 and ALPK1 inhibit differentiation of bi-potential tumor-initiating cells in human breast cancer

Abstract: Cancers are heterogeneous by nature. While traditional oncology screens commonly use a single endpoint of cell viability, altering the phenotype of tumor-initiating cells may reveal alternative targets that regulate cellular growth by processes other than apoptosis or cell division. We evaluated the impact of knocking down expression of 420 kinases in bi-lineage triple-negative breast cancer (TNBC) cells that express characteristics of both myoepithelial and luminal cells. Knockdown of ERN1 or ALPK1 induces bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…First, we identified a recurrent somatic missense ALPK1 mutation (p.V1092A) in the kinase domain of this alpha-kinase and demonstrated that this mutation can activate NF-κB signaling in cell reporter systems. Importantly, ALPK1 has previously been suggested to function as an oncogene 45 . Since kinases can be readily inhibited, this mutation represents a potential therapeutic target, which might be particularly advantageous in the advanced/metastatic setting, where effective treatments have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…First, we identified a recurrent somatic missense ALPK1 mutation (p.V1092A) in the kinase domain of this alpha-kinase and demonstrated that this mutation can activate NF-κB signaling in cell reporter systems. Importantly, ALPK1 has previously been suggested to function as an oncogene 45 . Since kinases can be readily inhibited, this mutation represents a potential therapeutic target, which might be particularly advantageous in the advanced/metastatic setting, where effective treatments have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…19 In triple mutation breast cancer, ALPK1 cells can modulate tumorigenic ability in vivo and in vitro. 18 However, there has been little evidence for an association between ALPK1 expression and clinicopathologic signatures in OSCC. Here, higher expression of ALPK was demonstrated in OSCC than in nontumor tissue.…”
Section: Discussionmentioning
confidence: 99%
“…15 ALPK1 has also been shown to play a role in the immune response, acting as a critical mediator for interacting between Helicobacter pylori, gram-negative bacteria, and cellecell contact. 16,17 A recent study provided evidence that APLK1 plays an inhibitory role in the differentiation of breast cancer, 18 and ALPK1 mRNA expression is correlated with lung and colorectal cancer progression, 19 However, the association of ALPK1 expression with clinicopathologic features and the cancer progression of OSCC remains unclear.…”
mentioning
confidence: 99%
“…Study by Jie Li and colleagues indicated that CBX4 was a critical regulator of tumor angiogenesis by governing HIF-1a protein [ 19 ]. Kanako Shinjo's findings demonstrated that expression CBX7 was associated with poor prognosis in ovarian clear cell adenocarcinoma via TRAIL-induced apoptotic pathway regulation [ 20 ]. However, the roles of distinct CBX members in contribution to tumorigenesis and development of BC are largely unknown.…”
Section: Introductionmentioning
confidence: 99%